Research and development of material feeder of drum type shredder - V. I. Zenikov (Сельскохозяйственные машины и технологии)
Fodder and straw harvesting units are equiped with material feeder of various designs which are applied for mass transportation from shredder. Transportation is carried out owing to action of centrifugal forces of the crushing drum and the air stream created by it. Thus, loss of the shredded mass on the way from a material feeder to the vehicle reach 15 percent. The main reason for the specified losses is blowing of mass particles from the air stream. A louver attachment of a new design decreases air stream intensity. The authors revealed possibility of losses reduction by the theoretical analysis and physical modeling of process of the air stream movement. Quasi-homogeneous substance inside a material feeder consists of the shredded straw and air which have density and pressure average on time and on canal section. To decrease air stream intensity the authors used the continuity and momentum equations. Thus, change of a substance mass expense or its density and speed was considered. This change was caused by separation of clean air. Tests of the developed material feeder showed that losses of the shredded straw were reduced by 40 percent. Thus a louver baffle fitted to the end of a material feeder decreased losses by 9 percent.